Nest and species description of the Southeast-Asian hover-wasp Eustenogaster gibbosa n. sp (Hymenoptera Vespidae) - Hashim, Rosli; Turillazzi, S.; Starr, C.K. (2006)
The females and males of Eustenogaster gibbosa, a new species of stenogastrine wasp from Peninsular Malaysia are described together with their nest.